EXPRESSION OF MENTAL STATE IN YOLDOSH ESHBEK'S POETRY - I.Kurbanbayev (Journals Park Publishing, 2022)
The article analyzes the degree of realization of feeling, the artistic-aesthetic nature of perception intuition at the level of poetic worldview. It talks about the presentation of the lyrical subject, the attitude to the object of the poetic image, the integrity of the mood and mental state in the text, the conflict between consciousness and artistic observation, and the improvement of the narrative technique. Although the personality of the poet and the nature of the philosophical goal are actually alternative concepts to each other, the poetic harmony of coincidence characterizes the art of words.
Keywords: emotion, artistic speech, narrative technique, aesthetic analysis, evaluation criterion, mental state, general mood, philosophical generalization, perception intuition, literary interpretation, lyrical subject, object of poetic image, creator's concept, independence of expression, lyrical hero, artistic skill.